The Ontological Foundations of Islamic Psychology: A Critical Comparison with Western Psychology and Its Theoretical Implications - Kumara Adji Kusuma; Eko Hardi Ansyah (Academia Open, 2026)
General Background: Contemporary psychology has predominantly evolved within Western empiricist and materialist traditions that conceptualize human nature through biological, cognitive, and behavioral dimensions. Specific Background: In contrast, Islamic Psychology is grounded in an Islamic worldview that understands human beings as an ontological unity comprising ruh, qalb, nafs, ‘aql, and jasad, each possessing distinct ontological status. Knowledge Gap: Despite increasing applied research in Islamic counseling and psychotherapy, the ontological foundations distinguishing Islamic Psychology as an autonomous scientific paradigm remain insufficiently articulated. Aims: This study aims to formulate a coherent ontological framework of Islamic Psychology and critically compare it with the dominant ontological assumptions of Western psychology. Results: Using a qualitative–philosophical library research approach, the study demonstrates that Islamic Psychology offers an integrative and hierarchical conception of the human soul that cannot be reduced to material or cognitive processes, while Western psychological paradigms largely operate within reductionist ontologies. Novelty: The study systematically articulates the ontological structure of ruh, qalb, nafs, ‘aql, and jasad as foundational elements of Islamic Psychology, positioning them as constitutive realities rather than symbolic constructs. Implications: This ontological clarification provides theoretical, methodological, and practical foundations for positioning Islamic Psychology as a philosophically autonomous and complementary paradigm within global psychological discourse, particularly in addressing spiritual and existential dimensions of human well-being. Highlights:  Islamic Psychology is grounded in an integrative ontological model uniting spiritual, rational, and bodily dimensions. Western psychological paradigms predominantly rely on materialistic and reductionist ontological assumptions. Ontological clarification strengthens Islamic Psychology as an autonomous and complementary scientific paradigm. Keywords: Islamic psychology; ontology; human soul; spirituality; Western psychology